-2(2x-3)=(-2)

Simple and best practice solution for -2(2x-3)=(-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x-3)=(-2) equation:


Simplifying
-2(2x + -3) = (-2)

Reorder the terms:
-2(-3 + 2x) = (-2)
(-3 * -2 + 2x * -2) = (-2)
(6 + -4x) = (-2)
6 + -4x = -2

Solving
6 + -4x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -4x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -4x = -2 + -6
-4x = -2 + -6

Combine like terms: -2 + -6 = -8
-4x = -8

Divide each side by '-4'.
x = 2

Simplifying
x = 2

See similar equations:

| 0.8x+5=0.2(40x) | | 19.00+1.50p=15.00+2.75 | | 5r^2-3r+15=0 | | (x-10)(x-10)=-121 | | 2/(-4)-3= | | 2x+8=8x+20 | | P=16*1+1 | | 3m-6z+6Z= | | 40-10h+9-4h= | | 12=-2g+44 | | 6x-23=54-x | | -4n-5=-3n+10 | | (6+9)+8= | | -2(-5-7q)= | | 3(y+7)=24 | | 2y-14=x | | -2(-2x-3)=(-2) | | -6B=-420 | | 6a-9=50 | | -8+a=27 | | 4u-12=56 | | 12=-x+9-5x | | 5x-6+x^2=2 | | 9t^2=3t | | (2w-1)(2w-1)x^2=21 | | -4n-2=3n+5 | | 9j+4=4j+14 | | 5/7ab-35b | | 3x-6=15x+18 | | 4y+5=y+9 | | 0.5x+10=1.8x+25.6 | | (4m+1)(m+11)=0 |

Equations solver categories